Local Flexibility within an Accountability System - Scafidi, Benjamin; Freeman, Catherine; DeJarnett, Stan (Education Policy Analysis Archives, 2001)
Over the past decade, several states have created comprehensive accountability systems designed to increase student learning in public schools. These accountability systems are based on "high-stakes" standardized testing of a state curriculum. Rewards and interventions for local educators are based largely upon students' performance on these tests. Using the recent accountability reforms in Georgia as a backdrop, this article considers the role of local flexibility within such an accountability system–flexibility over paperwork, resources, personnel, and curriculum for local educators. Increased flexibility for local educators is not merely an option in a world where local educators are subject to a comprehensive accountability system imposed by a state–it is a requirement for success. We make a case for providing local flexibility and provides a discussion regarding types of flexibility, vehicles for granting flexibility, and who should receive flexibility.